2003
DOI: 10.1143/jjap.42.1380
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Oxides of SiC on Carbon Nanotube Formation by Surface Decomposition

Abstract: We present consistent theoretical studies of optically heterodyned polarization interferometry (OHPI) with noncollinear arbitrary polarized interacting beams in the framework of the cubic nonlinear optical susceptiblity formalism. Our theoretical treatment is based on the covariant tensorial approach introduced by F I Fedorov. We were able to derive the analytical expressions for the detected OHPI signal. Different methods for measuring the nonlinear susceptibility are also suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 16 publications
2
32
0
Order By: Relevance
“…The plan view of the protrusion is round with a diameter of about 1 nm. It is reported that carbon nanotubes grow not only on (0001) surfaces but also on (0001) surfaces, when the native oxide is removed enough by HF treatment [10]. As the specimens used in this experiment are also treated by HF, it seems that the protrusions are the ends of carbon nanotubes in the initial stage growing on (0001) surfaces.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…The plan view of the protrusion is round with a diameter of about 1 nm. It is reported that carbon nanotubes grow not only on (0001) surfaces but also on (0001) surfaces, when the native oxide is removed enough by HF treatment [10]. As the specimens used in this experiment are also treated by HF, it seems that the protrusions are the ends of carbon nanotubes in the initial stage growing on (0001) surfaces.…”
Section: Resultsmentioning
confidence: 69%
“…6(e) and (f), string-shaped structures are transitionally generated on the C-terminated surface in the annealing process. As carbon nanotubes grow preferably on C-terminated surfaces than Si-terminated surfaces [9,10], the generation of string-shaped structures is considered to be restricted by the growth of carbon nanotubes. Considering the fact that string-shape structures are also generated on the C-terminated surface where step edges are not observed clearly after annealed up to 1000…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this process, not only highly pure but also vertically aligned CNT arrays were grown on the SiC surfaces. Following the first report, many research efforts have been made to understand the growth mechanism and to control the CNT growth in a well-defined way [13][14][15]. Up to now, it has been only shown that atmosphere is critical to the non-catalytic growth of CNTs on SiC.…”
Section: Introductionmentioning
confidence: 99%
“…The ends of the CNTs are closed, which indicates that the caps were formed by a lift-up of part of the graphene along the ½111 direction on SiC though the generation of pentagons and heptagons. Nagano et al 8,9 reported that CNTs can grow on both the Si-face and the C-face of SiC in a vacuum of approximately 10 À4 Torr. The growth rate of CNTs on the Si-face of SiC is about 65% of that on the C-face at 1700°C.…”
Section: Introductionmentioning
confidence: 99%